2016
DOI: 10.1111/cns.12506
|View full text |Cite
|
Sign up to set email alerts
|

The Cannabinoid CB1/CB2 Agonist WIN55212.2 Promotes Oligodendrocyte Differentiation In Vitro and Neuroprotection During the Cuprizone‐Induced Central Nervous System Demyelination

Abstract: SummaryAim and methodsDifferent types of insults to the CNS lead to axon demyelination. Remyelination occurs when the CNS attempts to recover from myelin loss and requires the activation of oligodendrocyte precursor cells. With the rationale that CB1 receptor is expressed in oligodendrocytes and marijuana consumption alters CNS myelination, we study the effects of the cannabinoid agonist WIN55212.2 in (1) an in vitro model of oligodendrocyte differentiation and (2) the cuprizone model for demyelination.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 58 publications
0
26
0
1
Order By: Relevance
“…In the prefrontal cortex (PFC), there was an increase in CB receptor 1 binding that coincided with reduced levels of monoacylglycerol lipase, extracellular signal‐regulated kinase, and cyclic adenosine monophosphate response element‐binding protein, which are all critically involved in CB signaling . WIN55 212.2, a CB receptor agonist, increased OPC proliferation in vitro, as well as MBP messenger RNA and protein expression in mice, whereas blocking the metabolism of endogenous CBs decreased OL excitotoxicity and demyelination in vitro, and preserved myelin integrity in a demyelinating mouse model . EtOH exposure alters CB ligands in several brain areas related to memory and addiction (e.g., PFC and amygdala).…”
Section: Etoh Impacts the Development Of Olsmentioning
confidence: 99%
“…In the prefrontal cortex (PFC), there was an increase in CB receptor 1 binding that coincided with reduced levels of monoacylglycerol lipase, extracellular signal‐regulated kinase, and cyclic adenosine monophosphate response element‐binding protein, which are all critically involved in CB signaling . WIN55 212.2, a CB receptor agonist, increased OPC proliferation in vitro, as well as MBP messenger RNA and protein expression in mice, whereas blocking the metabolism of endogenous CBs decreased OL excitotoxicity and demyelination in vitro, and preserved myelin integrity in a demyelinating mouse model . EtOH exposure alters CB ligands in several brain areas related to memory and addiction (e.g., PFC and amygdala).…”
Section: Etoh Impacts the Development Of Olsmentioning
confidence: 99%
“…Conversely, histological analysis of the demyelinated area revealed that CNS myelination was slightly compromised when 0.5 mg/Kg of WIN was administered. Similarly, a previous study revealed that the cannabinoid WIN at 0.5 mg/ Kg confers neuroprotection against demyelination while the administration of the drug at 1 mg/Kg aggravates the process 5 . Despite this, it is widely accepted that the cannabinoid receptors modulate the severity of demyelination in distinct experimental animal models 5,32 .…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, a previous study revealed that the cannabinoid WIN at 0.5 mg/ Kg confers neuroprotection against demyelination while the administration of the drug at 1 mg/Kg aggravates the process 5 . Despite this, it is widely accepted that the cannabinoid receptors modulate the severity of demyelination in distinct experimental animal models 5,32 . The administration of CPZ for three weeks led to a pronounced inflammatory reaction by activating the recruitment of microglia and astroglial cells in the demyelinated area 10,33 .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations